TOBACCO ISSUES IN THE 101ST CONGRESS (Tufts Archival Research Center, 2007)
Document listing the tobacco issues facing the 101st Congress. Includes excise taxes, fire safe cigarettes and airline smoking. Provides background on the issues followed articles, letters and quotes from people who support the tobacco industry's position.